Assessment of the comfort level of patients' companions in intensive care units and related factors - Zahra Velashjerdi Farahani; Mohsen Taghadosi; Zohreh Sadat (Kashan University of Medical Sciences, 2021)
Background: Patients' companions have a great role in intensive care units (ICUs). They act as patients' voice since a majority of patients are unable to communicate or make decisions. Objective: This study aims to investigate the comfort of patients' companions in ICUs and its related factors in a selected hospital in Kashan, Iran in 2019. Methods: This cross-sectional study was conducted on a convenience sample of 375 family members of patients recruited from the ICUs. Data collection instruments were a demographic questionnaire and companions comfort scale (ECONF). Data were analyzed with independent-samples t-test, one-way analysis of variance, Pearson's correlation analysis, and multiple linear regression analysis. Results: The mean score of companions' comfort was 179.02 ± 37. The multiple regression analysis indicated that foot or low back pain, Iranian nationality, being a first-degree relative, present more than once per day as the patient's companion, coma status of patients, and duration of hospitalization more than 1 week (P < 0.05) were associated with companions' comfort. Companions' gender, age, patient care alone, education level, income, history of an underlying disease, and connection to a ventilator were not related to the companions' comfort. Conclusion: The comfort score of patients' companions was above the moderate level. Some sociodemographic characteristics of the companions and clinical status of patients were related to comfort score. Further studies are necessary to assess cultural, demographic, and contextual aspects related to the comfort of patients' companions in the ICUs.